Analysis of Low–level Cadmium Exposure Effects on HUVECs (Human Umbilical Vein Endothelial Cells) Cell Viability and Morphology - Kristianningrum Dian Sofiana; Provisia Marthalita Y.W.; Khotimah Husnul; M Aris Widodo (Journal of Agromedicine and Medical Sciences, 2019)
Cadmium is a heavy metal that could be found in daily life. This metal has a toxicity, could contaminate the environment, and affect human health. The main aim of this research was to find the effect of low concentration Cadmium exposure in acute time toward HUVECs cell morphology and viability.In a True experimental research with in vitro model using HUVECs cell, HUVECs cell was divided into four groups. One control group (without CdCl2 induction) and three treatment groups with CdCl2 induction with various concentrations, 0,153 µg/L, 1,53 µg/L and 15,3 µg/L. The trial was repeated five times for each group. Cell morphology was observed with an inverted microscope. Cell viability was examined by MTT assay. Data were analyzed using Kruskal Wallis statistical test and continue with the Man Whitney test. Correlation test was using Spearman.Morphology of treatment group HUVECs cell induced by CdCl2 concentration 15,3 µg/L looked significantly different compared with control group (p<0.05). Cell viability on group HUVECs induced by CdCl2 15,3 µg/L significantly different compared with the control group. The correlation test resulted R= -0,665 with probability 0.001 which means the higher concentration of CdCl2 the lower the viability of cells. Cadmium in low concentration induces cell morphology change and reduce cell viability. Keywords: HUVEC, cadmium, cell morphology, cell viability.